Genetic diversity of cultured populations of giant freshwater prawn (Macrobrachium rosenbergii) in China using mtDNA COI and 16S rDNA markers. (October 2015) - Nguyen Thanh, Hai; Liu, Qigen; Zhao, Liangjie; Zhang, Hong; Liu, Jun; Nguyen Hai, Dang
Abstract: Partial sequences of mitochondrial DNA 16S rDNA and COI genes (395 bp and 498 bp respectively) were sequenced from samples of ten cultured populations of Macrobrachium rosenbergii (Giant Freshwater Prawn – GFP) in Zhejiang, Guangdong and Guangxi Provinces in China and two wild populations of GFP from Mekong River and Dongnai River in Viet Nam. Five haplotypes of 16S rDNA were identified in the 360 samples. The wild populations displayed nucleotide diversity ( π ) of 0.0008 and 0.0003, and genetic diversity ( h ) of 0.3030 and 0.1310 in the Mekong River and Dongnai River respectively. The cultured populations displayed no significant genetic diversity. COI sequences identified 17 haplotypes based on 21 polymorphic sites. At this marker, the 12 populations showed a range of h from 0.1290 to 0.6940 and π from 0.0003 to 0.0073. The largest genetic distance ( D a) among the 12 populations was 0.0065 (between ZJB and BT/DN populations) and the lowest D a was 0.0003 (between GDD and GDA populations). The wild populations had higher genetic diversity than the cultured populations, but three of cultured populations from Zhejiang (ZJA, ZJB and ZJC) had π higher than wild populations, because they originated from Thailand, Bangladesh and the Mekong River in Viet Nam. Highlights: Using mtDNA COI and 16S rDNA markers for genetic diversity evaluation in the cultured populations of Giant freshwater prawn (GFP) in China. The original source of the cultured population of GFP in China. Comparison of genetic diversity level between cultured and wild populations of GFP.